2013
DOI: 10.1007/s13594-013-0111-z
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the effect of initial concentrations on the drying kinetics of high solids milk using reaction engineering approach

Abstract: Many industries practice trial and error method to achieve optimum process conditions for desired powdered product quality in the event of fluctuations in the feed concentration, which happens more often than not and leads to wastage in product, time and energy. This paper presents the thermal-moisture drying histories for skim milk droplets from 37 to 43 wt%, in order to study the effects of initial solids variation on drying kinetics. The changes in droplet temperature, diameter and moisture content during d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
3
8
1
Order By: Relevance
“…However, a forced convection was necessary for any significant moisture removal, thus the activation energy has to increase if lower moisture content on dry basis was to be attained. Previous investigations found that SMP droplets of different initial solids, including those above 40.0 wt.% which were considered high concentration, exhibited similar drying behaviours at the later stage of convective dehydration and were able to be represented by an activation energy curve described by a common polynomial equation (Chew et al, 2013). This was similarly reflected in the MPC results (Fig.…”
Section: Comparison Of Drying Behaviours Of Mpc and Smp Dropletssupporting
confidence: 70%
See 2 more Smart Citations
“…However, a forced convection was necessary for any significant moisture removal, thus the activation energy has to increase if lower moisture content on dry basis was to be attained. Previous investigations found that SMP droplets of different initial solids, including those above 40.0 wt.% which were considered high concentration, exhibited similar drying behaviours at the later stage of convective dehydration and were able to be represented by an activation energy curve described by a common polynomial equation (Chew et al, 2013). This was similarly reflected in the MPC results (Fig.…”
Section: Comparison Of Drying Behaviours Of Mpc and Smp Dropletssupporting
confidence: 70%
“…The experimental data of SMP 20.0 wt.% and 40.0 wt.% were extracted from previous studies (Chew et al, 2013;Lin and Chen, 2002). The SMP powder contained 50.0 wt.% lactose, 33.5 wt.% protein, 0.7 wt.% fat, 12.0 wt.% ash and 3.8 wt.% moisture.…”
Section: Comparison Of Drying Behaviours Of Mpc and Smp Dropletsmentioning
confidence: 99%
See 1 more Smart Citation
“…As presented in the previous sections, the three-dimensional spray-drying model has been examined using the experimental data on single-stream mono-disperse droplet drying [5] and single droplet drying [30][31][32]47]. Upon obtaining reasonable results in the range of inlet temperatures of greater than 130 C, we decided to undertake some extra-calculations.…”
Section: Multiphysics Explorationmentioning
confidence: 99%
“…Previous experimental works suggested that the drying kinetics of a wide range of material have been well correlated with the REA. These materials include, but are not limited to, lactose, sucrose, maltodextrin, skim and whole milk, milk protein concentrate, cream, whey protein concentrate, docosahexaenoic acid emulsion, kiwifruit, and silica gel . Notably, these materials are generally characterized as skin‐forming or aggregate‐forming materials according to their particle‐forming behavior during drying .…”
Section: Introductionmentioning
confidence: 99%